Is Tobacco Taxation Regressive? Evidence on Public Health, Domestic Resource Mobilization, and Equity Improvements - Fuchs, Alan (World Bank, Washington, DC, 2019)
Tobacco taxes are recognized as an effective policy tool to reduce tobacco consumption and improve health outcomes; however, policy makers often hesitate to use them because of their possible regressive effects. This report assesses the ability of taxes on tobacco to improve future health and welfare outcomes, with a focus on their distributional impact and effects on the poor. In addition to adverse consequences on health and quality of life of smokers and their family members, tobacco-related illnesses cost billions of dollars in medical expenditures and losses in human capital and productivity, imposing heavy economic tolls on households and governments. Developing countries bear a high and increasing share of the economic burden of tobacco. However, traditional analyses often overlook the many economic benefits of reducing tobacco consumption. This report presents empirical findings using an extended cost benefit analysis (ECBA) methodology, to incorporate a more comprehensive view of the costs and benefits of increasing prices of tobacco on household welfare, and to assess their distributional impact by accounting for different consumer behaviors across income groups. Evidence for several countries shows that large price shocks on cigarettes can generate progressive and welfare-improving medium and long-term net impacts, that particularly improve welfare of lower-income households. Large shares of societies—and particularly the poor—can benefit from positive income gains by reducing tobacco-related medical expenses and avoiding premature deaths. Moreover, additional fiscal revenues generated may be used to further enhance measures to control tobacco and promote equity. Ultimately, the benefits and distributional impact of raising taxes on tobacco will depend on the ability of policy to understand and to leverage consumers' responses toward quitting tobacco, and to target comprehensive interventions to help the most vulnerable groups.